(untitled) (Нововведения Cовременного Научного Развития в Эпоху Глобализации: Проблемы и Решения, 2024)
It is apparent that,there has been dramatically high interest and requirement for learning foreign languages in the last several decades in order to achieve personal and professional development. Because of this reason, modern pedagogy of 21st century faces a challenging task to teach a foreign language peculiar and more effective methods and approaches. Therefore, this study purposes to explore some useful ways of teaching Russian and Uzbek as a foreign language (RFL and UFL).